PWE-015 Inflammatory Bowel Disease in The Elderly: Characteristics and Risk Factors for Disease. (17th August 2016) - Clough, J; Mendall, M; Braim, D; Hong, A
Abstract : Introduction: The number of patients presenting with IBD at older ages is increasing and the proportion of patients over the age of 60 is increasing as the IBD epidemic matures. There are only a few case series in literature concerning IBD presenting at older age ages. It is unknown whether the risk factors for disease differ compared to younger age groups. Methods: A database was established at CUH in 2002 and currently has 1326 subjects registered. Information was obtained pertaining to the subjects' age at diagnosis, exposure to established risk factors (smoking history and appendectomy), and disease profile. Their requirement for progression therapy was assessed, in terms of the need for immunosuppression, biological agents, and surgery. Patients who had required surgery for peri-anal disease only were not counted as having required surgery. Results: The characteristics of the subjects are shown in the table . A higher proportion of patients diagnosed over the age of 60 had UC compared to other age groups. In all in December 2015 303/1326 were aged over 60 giving a prevalence of 22.9% of all subjects with IBD versus an incidence in the over 60 age group of 11.5%. Male predominance is present at older ages of diagnosis of CD as opposed to female preponderance at younger ages. The female predominance in UC did not change across the age groups. Smoking although more common in older CD did not reach significance unlike at younger ages. Likewise appendectomy was not a risk factor in the over 60 s for CD unlike at younger ages. Older subjects were less likely to have had surgery or be on immunomodulators or biologics. For CD colonic disease was common in older subjects. Conclusion: CD diagnosed in later years is phenotypically different in terms of the associated risk factors and disease trajectory. It appears to run a more indolent course, with fewer patients requiring immunosuppressive or biologic therapy, and fewer surgical procedures. This raises the question as to whether old age CD disease is a different disease to that observed in younger subjects. The behaviour of UC does not demonstrate such marked differences with age of diagnosis. Disclosure of Interest: None Declared